2006
DOI: 10.1051/jp4:2006139005
|View full text |Cite
|
Sign up to set email alerts
|

Water in the Earth's atmosphere

Abstract: Abstract. Water is the key to our existence on this planet and it is involved in nearly all biological, geological, and chemical processes. Life on Earth depends very much on the remarkable properties of water. The availability of freshwater is for many regions one of the key concerns in connection with global climate change. The atmosphere contains only about 0.001% of the water available on our planet. Despite this small amount its horizontal and vertical distribution plays a key role in the global water cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 118 publications
(142 reference statements)
0
13
0
1
Order By: Relevance
“…About 90% of the water in the atmosphere emanates from the oceans, lakes, and other open water bodies (Quante and Matthias 2006). Through atmospheric transport and associated transfer processes, some of the water that evaporates over the oceans reaches the land and may precipitate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 90% of the water in the atmosphere emanates from the oceans, lakes, and other open water bodies (Quante and Matthias 2006). Through atmospheric transport and associated transfer processes, some of the water that evaporates over the oceans reaches the land and may precipitate.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the greatest variations in water vapor in space occur with increasing height above the surface; specifically, water vapor concentrations decrease markedly with increasing height. Important variations also occur close to the surface, where concentrations vary by more than three orders of magnitude from 10 ppm by volume (ppmv) in the coldest regions of the earth's atmosphere to as much as 5% by volume in the warmest regions (Quante and Matthias 2006). Most of the water vapor is concentrated in the tropical atmosphere, which contains more than 3 times as much water as the extratropical atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…For example, near the surface, where most water vapor resides, concentrations vary by more than 3 orders of magnitude, from 10 parts per million by volume in the coldest regions to as much as 5% in the warmest [Quante and Matthias, 2006]. The tropical atmosphere contains more than 3 times as much water vapor as the extratropical.…”
Section: Water Vapor Distributionmentioning
confidence: 99%
“…Globally, the hydrological cycle is characterized by the evaporation of about 500,000 cubic kilometers of water per year, of which 86% is from the oceans and 14% is from the continents [Quante and Matthias, 2006]. Most of the water that evaporates from the oceans (90%) is precipitated back into them, while the remaining 10% is transported to the continents, where the water precipitates.…”
mentioning
confidence: 99%
“…Satellite-based observations and pan evaporation data indicate that the quantity of moisture returned to the atmosphere by the process of evaporation is substantial and plays a significant role in governing the regional water budget. According to global estimates, the hydrological cycle involves an annual rate of evaporation of about 500 000 km 3 of water, around 86 % of which come from the oceans, with the remainder originating from the continents (Quante and Matthias, 2006). Using the Eulerian moisture tracking method in a global study, Van der Ent et al (2010) showed that about 40 % of terrestrial precipitation originates from land evaporation.…”
Section: Introductionmentioning
confidence: 99%